St. Kitts and Nevis : Staff Report for the 2000 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2001)
St. Kitts and Nevis is a small, open economy that is heavily dependent on tourism and other services, and some light manufacturing. The exchange rate peg to the U.S. dollar and strict limits on central government borrowing from the Eastern Caribbean Central Bank (ECCB) have helped maintain inflation at low levels, averaging below 2 percent in recent years. Labor force data are not collected in St. Kitts and Nevis, but shortages of highly skilled labor are reported to exist, and migrant workers are being employed in both agriculture and construction.